Characterization of three mycobacterial DinB (DNA polymerase IV) paralogs highlights DinB2 as naturally adept at ribonucleotide incorporation - Heather Ordonez; Maria Uson; Stewart Shuman (2014)
This study unveils Mycobacterium smegmatis DinB2 as the founder of a clade of Y-family DNA polymerase that is naturally adept at incorporating ribonucleotides by virtue of a leucine in lieu of a canonical aromatic steric gate. DinB2 efficiently scavenges limiting dNTP and rNTP substrates in the presence of manganese. DinB2's sugar selectivity factor, gauged by rates of manganese-dependent dNMP versus rNMP addition, is 2.7- to 3.8-fold. DinB2 embeds ribonucleotides during DNA synthesis when rCTP and dCTP are at equimolar concentration. DinB2 can incorporate at least 16 consecutive ribonucleotides. In magnesium, DinB2 has a 26- to 78-fold lower affinity for rNTPs than dNTPs, but only a 2.6- to 6-fold differential in rates of deoxy versus ribo addition (kpol). Two other M. smegmatis Y-family polymerases, DinB1 and DinB3, are characterized here as template-dependent DNA polymerases that discriminate strongly against ribonucleotides, a property that, in the case of DinB1, correlates with its aromatic steric gate side chain. We speculate that the unique ability of DinB2 to utilize rNTPs might allow for DNA repair with a 'ribo patch' when dNTPs are limiting. Phylogenetic analysis reveals DinB2-like polymerases, with leucine, isoleucine or valine steric gates, in many taxa of the phylum Actinobacteria.